2012
DOI: 10.1016/j.ocemod.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Ocean–atmosphere dynamics during Hurricane Ida and Nor’Ida: An application of the coupled ocean–atmosphere–wave–sediment transport (COAWST) modeling system

Abstract: a b s t r a c tThe coupled ocean-atmosphere-wave-sediment transport (COAWST) modeling system was used to investigate atmosphere-ocean-wave interactions in November 2009 during Hurricane Ida and its subsequent evolution to Nor'Ida, which was one of the most costly storm systems of the past two decades. One interesting aspect of this event is that it included two unique atmospheric extreme conditions, a hurricane and a nor'easter storm, which developed in regions with different oceanographic characteristics. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 76 publications
8
91
0
Order By: Relevance
“…This behaviour is consistent with other coupling atmosphere-ocean investigations under a high level of meteorological energy (e.g. Olabarrieta et al, 2012). In parallel, the wave field is modified by the feedback between wave and wind stress.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This behaviour is consistent with other coupling atmosphere-ocean investigations under a high level of meteorological energy (e.g. Olabarrieta et al, 2012). In parallel, the wave field is modified by the feedback between wave and wind stress.…”
Section: Discussionsupporting
confidence: 91%
“…The ocean-atmosphericwave online coupling was implemented in the finer domain (mesh O4 for the wave and circulation model, and mesh M4 for the meteorological model) where the scale of the coupling process due to cross-shelf winds may be more evident in the results. In this case, air-sea coupled effects are included considering the Taylor and Yelland formulation (Taylor and Yelland, 2001), for the ocean surface roughness modification due to the wave effect, and vortex force for the wave effects on currents (Olabarrieta et al, 2012). Table 1.…”
Section: Numerical Model and Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…The general relationships between the observed current velocity and the storm's translation speed and between the maximum current velocities and the Saffir-Simpson hurricane scale are also provided. Our results are congruent with recent studies (Olabarrieta et al, 2012;Warner et al, 2010;Yablonsky and Ginis, 2009;Zambon et al, submitted for publication) and provide useful tool for model validation. …”
Section: Discussionsupporting
confidence: 91%
“…In addition to current acceleration, existing modeling studies showed that TCs enhance drastically the upper ocean mixing and in turn affect the fluxes of heat and moisture across the air-ocean interface and change the dynamic height and sea surface temperature with the bias towards the right-side (Chang and Anthes, 1978;Chu et al, 2000;Jacob and Shay, 2003;Olabarrieta et al, 2012;Price, 1981;Price et al, 1994;Warner et al, 2010;Yablonsky and Ginis, 2009;Zambon et al, submitted for publication); and that TCs' passage affects upper ocean responses to the Kuroshio currents in the northwestern Pacific (Kuo et al, 2011;Tsai et al, 2008;Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%